Peningkatan Hasil Belajar PAKBP Materi Sepuluh Perintah Allah Dengan Metode PBL Kelas IV SD Negeri 14 Huta Hotang: (Problem Basic Learning) - Magdalena Silva Fiskayanti Samosir; Andarweni Astuti (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This study aims to improve the learning outcomes of fourth-grade students at SD Negeri 14 Huta Hotang in the subject of Catholic Religious Education and Character, specifically focusing on the topic "The Ten Commandments," through the implementation of the Problem-Based Learning (PBL) method. The objective is to enhance students' understanding of the Ten Commandments while incorporating the values of Pancasila. This Classroom Action Research (CAR) was conducted in two cycles, each consisting of planning, implementation, observation, and reflection on the Pancasila student profile. The results revealed significant improvements in students' learning and understanding of "The Ten Commandments." In the pre-cycle, the average student scores were below the Minimum Mastery Criteria (KKM), with seven students—five (62.5%) did not meet the standard, and two (37.5%) achieved mastery. After applying the Pancasila student profile, improvements were observed in both Cycle I and Cycle II, with Cycle II meeting the target outcomes. Besides academic improvements, the study also highlighted positive developments in various aspects of the Pancasila student profile, such as Faith in God Almighty and Noble Character, Global Diversity, Cooperation, Independence, Critical Thinking, and Creativity. The implementation of the PBL method was effective in improving students' learning outcomes in Catholic Religious Education and Character, particularly in understanding "The Ten Commandments," for fourth-grade students at SD Negeri 14 Huta Hotang.